Gold(I) and Silver(I) π-Complexes with Unsaturated Hydrocarbons - Motloch, Petr; Jašík, Juraj; Roithová, Jana (Organometallics, 2021)
Gold π-complexes have been studied largely in the past 2 decades because of their role in gold-catalyzed reactions. We report an experimental and theoretical investigation of the interaction between a wide range of unsaturated hydrocarbons (alkanes, alkynes, alkadienes, and allenes) and triphenylphosphine-gold(I), triphenylphosphine-silver(I), and acetonitrile-silver(I) cations. The bond dissociation energies of these complexes were determined by mass spectrometry collision-induced dissociations and their structures were studied by density functional theory calculations and infrared photodissociation spectroscopy. The results show that with the same phosphine ligand, gold binds stronger to the π-ligands than silver and thereby activates the unsaturated bond more effectively. Ligand exchange of phosphine by acetonitrile at the silver complexes increases the binding energy as well as the activation of the π-ligands. We also show that the substitution of an unsaturated bond is more important than the bond type.